Assets Structure Of Chandigarh Transport Undertaking - Goyal, Munish (Gyan Management Journal, 2020)
Assets are the resources owned by an undertaking. They represent ownership value which can be converted into cash. Tangible assets include fixed assets and current assets. Fixed assets have a physical form and are typically bought for production and supply of goods and services and provide a long term gain to the concern. They are not essentially fixed in all senses of word. Moreover they lose value as they are used. Current assets are meant to be converted into cash and are not depreciated. They basically indicate healthy liquidity position of the undertaking. Chandigarh Transport Undertaking (CTU) being a public transport unit of Chandigarh has to invest a large amount of funds in the fixed assets and have to hold a huge inventory as a part of current assets.